VARIABLE FONTS AND KINETIC TYPOGRAPHY IN THE WEB ENVIRONMENT - Кostenko, Ihor (Theory and practice of design, 2025)
The purpose of this study is to identify the key trends in the development of typography in web design and to analyze its influence on the formation of creative thinking and the creative potential of professionals in the field of visual communication. To achieve this goal, the technologies of variable fonts and kinetic typography are considered as the latest tools of digital design. The research methodology employs an interdisciplinary approach that combines technological, communicative, and cognitive methods to analyze typographic practices. A comprehensive study of the content-structural characteristics of variable fonts and kinetic typography has been carried out. The principles of OpenType Variable Fonts operation are examined, allowing for the dynamic adjustment of typographic parameters within a single file. The role of moving text in the multimedia environment is analyzed, with an emphasis on its expressive, communicative, and cognitive potential. Results. The research findings demonstrate that variable fonts contribute to optimizing interface design by increasing flexibility, adaptability, and reducing the load on digital platforms. They can be used to technically enhance the visual environment. Kinetic typography proves to be an effective tool for emotional impact, attention engagement, and the creation of interactive visual content. Moving text ensures dynamic expression of information through animation, which enhances message perception and enriches the visual language of web design. It has been established that both forms of typography – variable (static) and kinetic (dynamic) – interact and complement each other, laying the groundwork for the formation of innovative approaches to digital environment design. The scientific novelty lies in the fact that new aspects of applying typographic innovations in web design have been revealed. A comparative analysis of variable fonts and kinetic typography in the context of forming creative strategies for digital design has been conducted. It has been proven that the use of variable fonts enables more precise customization of the visual system to meet the requirements of responsive interfaces, while kinetic typography ensures a deeper emotional connection with the user. Practical relevance. The practical significance of the work lies in the application of principles for developing interfaces that combine technical efficiency with aesthetic appeal. These findings can be used by practicing web designers and digital communication specialists. The identified principles of implementing variable fonts and kinetic typography make it possible to create personalized, adaptive, and emotionally engaging digital environments. This contributes to the improvement of visual communication and expands the creative design toolkit in the context of digital transformation.